Government Spending and Economic Growth: Keynes or Wagner for Cameroon? ARDL/T-Y-VAR Approach - Ndam Mama; Tanyi Pamela Nyugha; Awemu Jonah Wayih; Gildas Dohba Dinga (Law and Economy, 2022)
This study had as primordial objective, to empirically investigate the nature of the link between government expenditure and economic growth in Cameroon from 1977-2018. To realise this objective, data were collected from the World Bank World Development Indicators and the ARDL technique was employed to examine the short and long run effects of government expenditure on economic growth in Cameroon. Then the VAR model, following the Toda-Yamamoto (1995) specification which is an ameliorated version of the traditional VAR model developed by Sims (1980) and Granger (1969) were employed to examine the nature of the link between the variables. The outcome from the ARDL model indicates that there is short run significant negative effect of government expenditure on economic growth while in the long run, there is a positive and insignificant effect. The result from the VAR model shows that there is a unidirectional causal relationship from growth to government expenditure. This result supports the Wagner’s law of expanding state activities for Cameroon. The findings suggest that instead of involving in increased spending as a means to guarantee sustainable growth, government should focus on policies that would create the enabling environment for growth to thrive like control of corruption and reforms in the financial sector to attract more private investment and the strengthening of state institutions.